Budgetary Control and Organizational Performance in Municipal Local Governments in Uganda: A Case of Kabale Municipal Council. - Akankwasa, Fidelis (Kabale University, 2024)
The purpose of the study was to examine the effect of budgetary control and organizational performance in Kabale Municipal Local Government. The study was guided by three (3) objectives namely: to assess the effect of budget planning on the organizational performance in Kabale Municipal Council; to examine the effect of budgetary challenges on the organizational performance of Kabale Municipal Council; and, to establish the relationship between budgetary control and organizational performance of Kabale Municipal Council. This study adopted a descriptive research design. It involved quantitative and qualitative methods. A sample of 163 were selected using simple random sampling and census sampling techniques. The quantitative and qualitative data from the respondents were analysed using SPSS version 23.0 and thematic analysis respectively. The study found out that budgetary planning control has a positive significant relationship with trainees’ employability r =. 0. 762** P≤.01). In addition, results showed budgetary challenges positively and significantly related to trainees’ employability (r =. 456, P≤.01). Lastly, there was also a significant positive relationship between Strategies to improve budgetary challenges (r =.399 P≤.01). The study concludes that; budgetary control has an influence on organizational performance in Kabale Municipal Local Government. The study recommends that for Kabale Municipal Council to perform well as the standing order says, budgetary controls should be put under serious consideration. Kabale Municipal Council should bridge the gap between the theory and practice of strategic management by addressing the budgetary challenges. The main emphasis should be on budget formulation, budget implementation, and funding limitations. This will help Kabale Municipal Council to excel in the effective implementation of government programs at Kabale Municipal Council, there is a need to understand the contributions of good budgeting practices on the organizational performance. This will help Kabale Municipal Council to always establish the persons who are supposed to participate in the budgetary process for purposes of enhancing organizational performance at Kabale Municipal Council.